Immunosuppressive drugs prevent a rapid dephosphorylation of transcription factor NFAT1 in stimulated immune cells. - Shaw, K T (1995)
The immunosuppressive drugs cyclosporin A and FK506 interfere with the inducible transcription of cytokine genes in T cells and in other immune cells, in part by preventing the activation of NF-AT (nuclear factor of activated T cells). We show that transcription factor NFAT1 in T cells is rapidly dephosphorylated on stimulation, that dephosphorylation occurs before translocation of NFAT1 into the cell nucleus, and that dephosphorylation increases the affinity of NFAT1 for its specific sites in DNA. Cyclosporin A prevents the dephosphorylation and the nuclear translocation of NFAT1 in T cells, B cells, macrophages, and mast cells, delineating at least one mechanism that contributes to the profound immunosuppressive effects of this compound.